2019
DOI: 10.1097/scs.0000000000005316
|View full text |Cite
|
Sign up to set email alerts
|

The Esthetic Difference of Chinese Beauty Evaluated by Two Different Human Races Based on Three-Dimensional Average Face Analysis

Abstract: The aim of this study was to establish a new method of facial soft tissue analysis based on 3dMDface system and to find the different esthetic preferences of Chinese beauties from the Chinese and Indian evaluators perspective. Methods: Three-dimensional facial images of 242 females and 168 males were evaluated and ranked by 8 Chinese and nine Indians using a 10-point visual analog scale (VAS). Total 120 subjects in 2 panels (from Chinese perspective and Indian perspective) including 30 male and 30 female faces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…50 A recent 3D study confirmed these earlier 2D preferences within an Asian population. 16 In the present study, the individual perception of 3D profile variation rated by orthodontists, maxillofacial surgeons, plastic surgeons, dentists and laypeople was measured. A 3D average face was generated from a group of Class I profiles, young adult, males and females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…50 A recent 3D study confirmed these earlier 2D preferences within an Asian population. 16 In the present study, the individual perception of 3D profile variation rated by orthodontists, maxillofacial surgeons, plastic surgeons, dentists and laypeople was measured. A 3D average face was generated from a group of Class I profiles, young adult, males and females.…”
Section: Discussionmentioning
confidence: 99%
“…43,[53][54][55][56] Further, the majority of studies considering facial attractiveness tended not to involve raters from different professional backgrounds. 16,[57][58][59][60] Additionally, a standard method to define and rate facial attractiveness has not been used across studies, although it has been recommended that a standardised approach towards facial type acquisition, raters panel and validated outcome measures be used. 61 The influence of occupation and socioeconomic status on the perception of facial attractiveness remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the present study, surgery simulations can be carried out using the CAD module by inputting the ossicles' HRCT data with lesions or defects (14). Either mirror imaging or the use of the normal ossicular morphology as a standard can then be employed for the virtual realization of the anatomical repair of the defective malleus, incus, or even stapes (15)(16)(17)(18). The application of suitable ossicular prosthesis materials in TDP rapid prototyping for the accurate repair of the ossicles is expected to change conventional ossicular reconstruction's current status, making it less time-consuming and effort-intensive, and more accurate.…”
Section: A B C Dmentioning
confidence: 99%
“…A study 21 The most important aspect of the current study is its uniqueness in the Pakistani dental literature since, to the best of our knowledge, it is the first study establishing the opinion of Pakistani population regarding lip profile preference specifically. The small sample size and less heterogeneity of the sample are limitations of the current study.…”
Section: P R O V I S I O N a L L Ymentioning
confidence: 99%